Analisis Program Makan Gratis Prabowo Subianto Terhadap Strategi Peningkatan Motivasi Belajar Siswa di Sekolah Tinjauan dari Perspektif Sosiologi Pendidikan - Ajeng Atikah Merlinda; Yusmar Yusuf (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The Free Nutritious Meal Program (MBG) is a strategic initiative aimed at improving the nutritional quality and learning motivation of students in Indonesia. This program is based on data showing that 41% of students in Indonesia experience hunger while studying, which negatively impacts their concentration and academic achievement. MBG not only targets school children, but has also been expanded to include toddlers, pregnant women, and breastfeeding mothers. The government has allocated a budget of IDR 71 trillion in the 2025 Draft State Budget for the initial phase of this program, which is planned to start on January 2,A 2025. Through critical discourse analysis developed by Teun A. Van Dijk, this study will analyze the structure and discourse strategies used in the MBG program, as well as how public perceptions of this program are formed and influence students' attitudes and behaviors at school. Data were collected through non-participant observation in schools involved in the program as well as documentation from various social media and related news. The results of this study are expected to provide a clearer picture of the impact of the program on students' learning motivation and its implications in the context of education in Indonesia. Thus, this study can contribute to the development of more effective education policies in Indonesia.